Fathers, families, and the state in France, 1914-1945 - Childers, Kristen Stromberg (Cornell University Press, 2003)
"The debate on men as gendered beings, Childers demonstrates, is central to the political, social, and cultural history of France in the modern age. The father figure became a focus as participants from all classes and across the political spectrum debated what was wrong with the French family and what policies were needed to remedy the problem. Childers examines how these policies were implemented, what they reveal about the development of the welfare state in France, and how they help explain the importance of Vichy in twentieth-century French history. Twenty-eight illustrations, including fifteen photographs, many never previously published, complement her argument."--Jacket